Association between oncology clinical pathway utilization and quality and cost outcomes in patients with metastatic solid tumors. Issue 28 (1st October 2022) - Liu, Ying; Mullangi, Samyukta; Chen, Xiaoxue; Pham, Timothy; Debono, David Joseph; Fisch, Michael Jordan; Gordon, Aliza; Hershman, Dawn L.
Abstract : 430 Background: Anticancer drug regimens that are approved by accepted drug compendia and also considered high value based on their efficacy, toxicity, and costs are designated as "on-pathway" for a national commercial payer. This study compared quality and cost of cancer care among patients with metastatic solid tumors treated in the first line setting who were prescribed on- vs. off-pathway regimens. Methods: Using administrative claims data and prior authorization data from a national commercial payer, we identified 8, 357 commercially insured or Medicare Advantage adult patients with solid tumor cancers including breast, lung, colorectal, pancreatic, melanoma, kidney, bladder, gastric, or uterine cancer, who were prescribed first-line anti-cancer regimens in the metastatic setting from 2018 to 2021. Patients were classified into on- vs. off pathway group based on the initial anticancer regimen that was prescribed. On-pathway status was prospectively defined by a panel of practicing oncologists based on review of curated evidence and general application of relative clinical value frameworks accepted in the field. We compared post–6-month quality-of-care outcomes including chemotherapy-related avoidable hospitalizations, emergency room (ER) visits, immune-related adverse events (IRAEs) such as endocrinopathies owing to immune checkpoint inhibitors, need for supportive drugs such as granulocyte colony stimulating factor, and cost outcomes between groups. Generalized linear models were used to assess the association between on-pathway regimens and outcomes adjusting for key patient demographics, clinical and provider characteristics. Results: A total of 5, 453 (65.3%) patients were prescribed on-pathway regimens. Both groups had similar age (60.1 vs. 59.6, p = 0.06) and ECOG performance status (0.63 vs. 0.62, p = 0.40), with more females in the off-pathway group (54.6% vs. 57.3%, p = 0.02). There was no statistically significant difference in chemotherapy-related avoidable hospitalizations, IRAEs and need for supportive drugs between the two groups after modeling adjustment. However, patients treated on-pathway had higher rates of chemotherapy-related avoidable ER visits (18% vs. 15%, adjusted odds ratio: 1.16, 95% confidence interval (CI): 1.01 to 1.33, p = 0.03). Patients in the on-pathway group had significantly lower 6-month anticancer treatment cost (adjusted cost difference: -$10410, 95% CI: -$14935 to -$5886, p < 0.01), resulting in an overall lower total healthcare costs (adjusted cost difference: -$12826, 95% CI: -$18879 to -$6773, p < 0.01). Conclusions: Pathway regimens for metastatic solid tumors were associated with reduced total healthcare costs and similar quality of care compared with off-pathway regimens. These findings support the use of high value, evidence-based regimens for metastatic cancer patients.